Promosi Pegawai Negeri Sipil Dalam Jabatan Struktural Di Badan Kepegawaian Daerah Kota Ternate - Fatum, Hidayat; Tulusan, Femmy; Palar, Novie (Sam Ratulangi University, 2017)
Abctract: The purpose of this research is to find out how the promotion of CIVIL SERVANTS in the Office of the Civil Service Agency in the area of structural Ternate city. This study uses qualitative methods. Informant this study as much 6 officials/employees at BKD, i.e.: Secretary (1 person), head (2), the head of the subfields (1 person), CIVIL SERVANTS ever in the promotion (1 person), and CIVIL SERVANTS have never been in the promotion (1 person). Data collection techniques used are interviews. Data analysis was done with a qualitative analysis techniques, interactive analysis models from Miles and Hubernann. Based on research results drawn conclusion:(I) requirements for the promotion of structural officials (i.e. rank/category, educational level, work achievement, competency, training, structural seniority, experience, and age) applied with a fairly consistent and objective enough. (2) Promotion of structural officials also consider it pretty consistently and fairly objective factor of dedication and loyalty, and morality. Shove off from the results of this research, suggested:(I) forward, the process of the promotion of structural officials at BKD Ternate city be done openly through the term of the auction system was implemented in some areas. (2) Team Baperjakat be more rigorous and objective selection process in the promotion of CIVIL SERVANTS in the structural position in accordance with the mandate of the ACT. No. 5 Year 2014.Keywords: Promotion Of Civil Servants, The Structural Position